n → ∞ lim [ 2 ( n + 1 ) ] 2 [ ( 2 n + 1 ) ! ] 2 r = 0 ∏ n [ ( 2 ( r + 1 ) ) 2 ( ( 2 r + 1 ) 2 − x 2 ) ]
Denote the limit above as L ( x ) . If the coefficient of x 4 8 of L ( x ) is C , what is the value of ⌊ 1 0 4 1 2 ! 4 8 ! C ⌋ ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same method +1
What was the motivation for the title of the problem?
Log in to reply
Euler used this to justify the solution for the Basel problem. As with a lot of his proofs(that i know of), the only thing that was involved was high school mathematics.
Log in to reply
Until you go about trying to justify(rigorously) his factorisation that is. :D
But yea, it fits.
Log in to reply
@Shashwat Shukla – Yeah, Euler's proof was wrong technically, until he extended it later.
But, f ( x ) = x sin ( x ) e x ,will also have the same factorisation,won't it?
L ( x ) = c o s ( π x / 2 )
The coefficient of x 4 8 in L ( x ) = cos 2 π x is C = 2 4 8 ⋅ 4 8 ! π 4 8 , which is already quite small; it is approximately 2 ⋅ 1 0 − 5 2 . Then ⌊ 1 0 4 ⋅ 1 2 ! C ⌋ = 0 .
Log in to reply
Thank you for pointing out my mistake sir! I missed out a 4 8 ! . I have corrected it. Sorry for the inconvenience.
Problem Loading...
Note Loading...
Set Loading...
Consider the function, f ( x ) = c o s x
Euler factorised x s i n x as x s i n x = ( 1 − π x ) ( 1 + π x ) ( 1 − 2 π x ) ( 1 + 2 π x ) . . .
Thus, x s i n x = r = 1 ∏ ∞ ( 1 − ( r π ) 2 x 2 )
Similarly, the roots of c o s x are 2 π , 2 − π , 2 3 π , 2 − 3 π . . .
We can then write, f ( x ) = c o s x = r = 1 ∏ ∞ ( 1 − ( 2 ( 2 r − 1 ) π ) 2 x 2 ) = r = 1 ∏ ∞ ( 1 − ( ( 2 r − 1 ) π 2 x ) 2 )
Now, let x = 2 π y
We have: f ( 2 π y ) = r = 1 ∏ ∞ ( 1 − ( ( 2 r − 1 ) y ) 2 )
A little fiddling around should convince you that this is indeed the expression given in the question.
Thus, L ( x ) = c o s ( 2 π x ) .
To find the coefficient of x 4 8 , note that the Taylor series for cosx is:
c o s ( x ) = 1 − 2 ! x 2 + 4 ! x 4 . . . 4 8 ! x 4 8 . . .
The rest is trivial.